2012
DOI: 10.5433/1679-0359.2012v33n1p115
|View full text |Cite
|
Sign up to set email alerts
|

Colonização micorrízica, densidade de esporos e diversidade de fungos micorrízicos arbusculares em solo de Cerrado sob plantio direto e convencional

Abstract: ResumoA busca da sustentabilidade na produção agrícola através de manejos conservacionistas, como o sistema plantio direto, tem favorecido os processos bioquímicos do solo como dos fungos micorrízicos arbusculares (FMAs), os quais promovem um aumento expressivo da superfície específica de absorção do sistema radicular das plantas. Sendo assim, o objetivo deste trabalho foi avaliar a colonização micorrízica, densidade de esporos e a diversidade de FMAs na rizosfera de milho e soja cultivados sob plantio direto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 24 publications
2
14
0
8
Order By: Relevance
“…Values were not significantly different. In the work of Angelini et al (2012), it was observed that in the 0 to 5 cm layer there was a significant effect when associated with crops and vegetation cover, thus it is possible to explain the highest values in the AS and layer of 5 to 10 for crop species. Table 3 shows the average of fungal CFU in relation with the time of system implantation, demonstrating that the systems that were implanted 5 years ago were superior to the value found in the newly implanted systems.…”
Section: Resultsmentioning
confidence: 99%
“…Values were not significantly different. In the work of Angelini et al (2012), it was observed that in the 0 to 5 cm layer there was a significant effect when associated with crops and vegetation cover, thus it is possible to explain the highest values in the AS and layer of 5 to 10 for crop species. Table 3 shows the average of fungal CFU in relation with the time of system implantation, demonstrating that the systems that were implanted 5 years ago were superior to the value found in the newly implanted systems.…”
Section: Resultsmentioning
confidence: 99%
“…Vale ressaltar que o interesse em estudos sobre a biologia, diversidade e atividade dos microorganismos do solo está cada vez maior, principalmente com os que cumprem função na ciclagem de nutrientes e/ou produtividade dos ecossistemas, como por exemplo, as micorrizas arbusculares (ANGELINI et al, 2012). COSTA, N.L.…”
Section: Introductionunclassified
“…This depth was chosen based on the methodology proposed by other authors and due to the highest occurrence of spores in this soil layer Angelini et al, 2012).…”
Section: Area Of Study and Soil Collectionmentioning
confidence: 99%